2019
DOI: 10.1021/acs.jpclett.9b00864
|View full text |Cite
|
Sign up to set email alerts
|

pJ-Level Energy-Consuming, Low-Voltage Ferroelectric Organic Field-Effect Transistor Memories

Abstract: Ferroelectric organic field-effect transistors (Fe-OFETs) have attracted considerable attention because of their promising potential for memory applications, while a critical issue is the large energy consumption mainly caused by a high operating voltage and slow data switching. Here, we employ ultrathin ferroelectric polymer and semiconducting molecular crystals to create low-voltage Fe-OFET memories. Devices require only pJ-level energy consumption. The writing and erasing processes require ∼1.2 and 1.6 pJ/b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 45 publications
(74 reference statements)
0
26
0
Order By: Relevance
“…Besides, under the effective modulations of interactions at semiconductor/dielectric interfaces, the prominent features combined with the unique merits of material versatility and ease of processing allow OFETs suitable for various potential functional applications, such as photoelectric detection, biosensing, and data storage. Pei et al scaled down the organic functional layers to a 2D limit with good uniformity over a large area [123]. The quasi-2D ferroelectric dielectric layers are beneficial for low-voltage operations.…”
Section: Modulations Of Interactions At Semiconductor/dielectric Intementioning
confidence: 99%
“…Besides, under the effective modulations of interactions at semiconductor/dielectric interfaces, the prominent features combined with the unique merits of material versatility and ease of processing allow OFETs suitable for various potential functional applications, such as photoelectric detection, biosensing, and data storage. Pei et al scaled down the organic functional layers to a 2D limit with good uniformity over a large area [123]. The quasi-2D ferroelectric dielectric layers are beneficial for low-voltage operations.…”
Section: Modulations Of Interactions At Semiconductor/dielectric Intementioning
confidence: 99%
“…For example, Xu et al utilized a P(VDF-TrFE-CTFE) film with low coercive field to develop a Fe-OFET NVM with low operating voltage. Construction of the compound gate dielectric layer was an ultrathin P(VDF-TrFE-CTFE) film sandwiched in between two layers ultrathin high-κ AlO x [112,114]. The sandwich-structured dielectric layer made a contribution to reduce the operating voltage, depress the gate leakage and improve the mobility.…”
Section: Other Low-power Consumption Devicesmentioning
confidence: 99%
“…The sandwich-structured dielectric layer made a contribution to reduce the operating voltage, depress the gate leakage and improve the mobility. Therefore, the device exhibited a low operating voltage of 4 V and the on-off ratio was over 10 2 at the low P/E voltages of ±4 V. In addition, Pei et al reported ultra-low-powerconsumption memory, namely, C 8 -BTBT-based Fe-OFET NVMs with a high-κ AlO x and ultra-thin P(VDF-TrFE) hybrid dielectric, to reduce the operating voltage and promote the data switching [112]. The device exhibited low voltage, fast operation, and satisfactory performance of low-power consumption due to the ultrathin ferroelectric and the high-quality 2D molecular crystals with excellent charge transport characteristics.…”
Section: Other Low-power Consumption Devicesmentioning
confidence: 99%
“…The thicknesses of the 1L and 2L films were ≈2.46 and 2.97 nm, respectively, which were in good agreement with the previously reported thickness. [24,50] The thickness difference between the 1L and 2L C 8 -BTBT films results from the variation in the molecular-substrate interaction for the 1L and 2L layers. [17] The 1L molecular-substrate interaction is stronger than the 2L molecular-substrate interaction, leading to the packing of 2L molecules being more upright than that of 1L molecules.…”
Section: Patterning 2d Organic Crystalline Semiconductors Via Thermalmentioning
confidence: 99%